2019
DOI: 10.3892/ol.2019.10205
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib combined with chemotherapy in patients with previously treated advanced breast cancer: An observational study

Abstract: Locally advanced or metastatic disease accounts for the majority of breast cancer-associated cases of mortality. Treatment options for patients with locally advanced or metastatic disease are limited. The current study aimed to explore the efficacy and safety of apatinib combined with chemotherapy in patients with previously treated advanced breast cancer in real-world clinical practice. A total of 85 patients with advanced breast cancer, who had previously been exposed to anthracyclines or taxanes, received c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 40 publications
1
26
1
1
Order By: Relevance
“…In 56 patients with TNBC, the mPFS and OS were 3.3 months and 10.6 months, respectively; the ORR was 10.7% ( 16 ). In addition, results from an observational study investigating the anti-tumor activity and safety of apatinib combined with chemotherapy in 85 heavily and repeatedly treated ABC patients in clinical practice revealed an mPFS and mOS of 4.4 months and 11.3 months, respectively ( 32 ). A subgroup analysis of the patients with TNBC revealed an mPFS and mOS of 5.2 months and 11.4 months compared with an mPFS and mOS in the non-TNBC group of 4.3 months and 11.3 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In 56 patients with TNBC, the mPFS and OS were 3.3 months and 10.6 months, respectively; the ORR was 10.7% ( 16 ). In addition, results from an observational study investigating the anti-tumor activity and safety of apatinib combined with chemotherapy in 85 heavily and repeatedly treated ABC patients in clinical practice revealed an mPFS and mOS of 4.4 months and 11.3 months, respectively ( 32 ). A subgroup analysis of the patients with TNBC revealed an mPFS and mOS of 5.2 months and 11.4 months compared with an mPFS and mOS in the non-TNBC group of 4.3 months and 11.3 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Apatinib is an oral, highly selective VEGFR2 antagonist, and was approved by the China Food and Drug Administration for use as a single agent in patients with advanced gastric or gastroesophageal junction adenocarcinoma after second line chemotherapy failure [ 5 ]. In addition, apatinib has also showed good clinical efficacy in a variety of solid tumors, including lung [ 6 ], liver [ 7 ], ovarian [ 8 ], breast [ 9 ], colorectal [ 10 ] and bone soft tissue sarcoma [ 11 ]. Preclinical studies demonstrated that apatinib affect VEGF-mediated cell proliferation and migration in cholangiocarcinoma cell [ 12 ], however, clinical use of apatinib in BTC was rarely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…As another emerging agent of angiogenesis in China, apatinib has been approved as salvage treatment in patients with gastro-esophageal adenocarcinoma or advanced gastric adenocarcinoma as third-line or further lines choice. [ 5 , 6 ] Apatinib is widely attempted for the salvage therapy in multiple types of advanced/metastatic solid carcinomas including hepatocellular carcinoma, [ 15 ] breast cancer, [ 16 ] colorectal cancer, [ 17 ] and NSCLC. [ 18 ] However, reducing the dose of apatinib is adopted in majority of researches because of the potentially severe adverse events.…”
Section: Discussionmentioning
confidence: 99%